EFFECT OF TOXOCARA CANIS SECOND STAGE LARVAE ON THE HOST IMMUNE SYSTEM (Journal of Sciences, Islamic Republic of Iran)
We have studied functional alteration of immunocytes in mice following inoculation of Toxocara canis second stage larvae. Results indicated depression of lymphocyte blastogenesis in response to concanavalin-A, phytohemagglutinin and allogeneic non B-cells; however, B-cell polyclonal activation was not affected as indicated by the production of total IgG. In contrast, frequency of antibody secreting cells was reduced. Similarly, interleukin-1 and interleukin-2 production were not affected by Toxocara canis infection. Furthermore, spleen cells of infected mice synthesized more prostaglandin E than uninfected animals. This data suggests that Toxocara canis infection induces suppression of both cell mediated and humoral immunity; perhaps due to an increase of prostoglandin E2 production.